2019
DOI: 10.1111/add.14651
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of five self‐report screening instruments for substance use in pregnancy

Abstract: Background and aimsThe accuracy of current screening instruments for identification of substance use in pregnancy is unclear, particularly given methodological shortcomings in existing research. This diagnostic accuracy study compared five existing instruments for ability to identify illicit drug, opioid and alcohol use, under privacy expectations consistent with applied practice and using a gold standard incorporating toxicological analysis.DesignProspective cross‐sectional screening accuracy study.SettingThr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…cognitive-behavioral therapy; 52 however, availability of screening tests with both a high sensitivity and specificity for pregnant women remains an issue. 58 As expected and previously reported, 5 early pregnancy was associated with use and frequency of use in the past 30 days. This finding is of concern as use in the first months of pregnancy may compromise embryonic development, specifically neuronal development.…”
Section: Dovepresssupporting
confidence: 84%
See 1 more Smart Citation
“…cognitive-behavioral therapy; 52 however, availability of screening tests with both a high sensitivity and specificity for pregnant women remains an issue. 58 As expected and previously reported, 5 early pregnancy was associated with use and frequency of use in the past 30 days. This finding is of concern as use in the first months of pregnancy may compromise embryonic development, specifically neuronal development.…”
Section: Dovepresssupporting
confidence: 84%
“…Based on our findings, as well as other previous literature [49][50][51] co-use of cannabis with other substances, occurs among pregnant women; therefore, additional screening and intervention development and implementation efforts are a priority. Typically, substance use screening and intervention are not integrated into routine prenatal care, [52][53][54][55][56][57][58] and pregnant women, who are more likely to be in need for these services, are less likely to receive them compared to non-pregnant women. 55 In addition, drug screening and effective interventions for cannabis use prevention during pregnancy are underdeveloped.…”
mentioning
confidence: 99%
“…Utilization of verbal validated screening tools, such as 4P's, NIDA Quick Screen, and CRAFFT to identify drug and alcohol use among pregnant women is recommended by ACOG (12). A recent study validated five commonly used screening tools against biological samples and found that sensitivity and specificity for each screening tool differed by substance and that no tool had both high sensitivity and specificity (33).…”
Section: Discussionmentioning
confidence: 99%
“…26,40 The World Health Organization (WHO) guidelines for the identification and management of substance use and substance use disorder during pregnancy list the Substance Use Risk Profile-Pregnancy (SURP-P) scale, 41 the proprietary 4P's Plus © , 42 and the National Institute on Drug Abuse (NIDA) Quick Screen-Modified Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST) 43 as potential screening measures for pregnant women, even though not all of these instruments had been evaluated among that population at the time of its recommendation. 44 Several recent studies have evaluated the accuracy of various screening tools for prenatal substance use. In one prospective cross-sectional study conducted in Baltimore, MD, with 500 pregnant women, stratified by trimester and use of prenatal care, researchers administered three index tests and compared them to reference tests.…”
Section: Screening For Prenatal Substance Usementioning
confidence: 99%